The big battle - Scollon, Bill (Step into reading., 2014)
When he finds himself in the grips of a criminal plot that threatens to destroy San Fransokyo, robotics prodigy Hiro Hamada joins forces with a reluctant team of first-time crime fighters on a mission to save the city.